2006
DOI: 10.1108/09564230610651570
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the link between employee satisfaction and store performance in a retail environment

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Gómez et al (2004) illustrated that retailers can affect store revenues by managing customer satisfaction. Keiningham et al (2006) showed a positive relationship between employee satisfaction and store profitability. Based on these arguments, the following hypothesis is proposed:…”
Section: Perceived Market Performancementioning
confidence: 87%
See 1 more Smart Citation
“…Gómez et al (2004) illustrated that retailers can affect store revenues by managing customer satisfaction. Keiningham et al (2006) showed a positive relationship between employee satisfaction and store profitability. Based on these arguments, the following hypothesis is proposed:…”
Section: Perceived Market Performancementioning
confidence: 87%
“…Anderson & Sullivan, 1993;Etezadi-Amoli & Farhoomand, 1996;Gelderman, 1998;Gómez et al, 2004;Keiningham, Aksoy, Daly, Perrier, & Solom, 2006). Anderson and Sullivan (1993) addressed the simultaneous estimation of antecedents and consequences of customer satisfaction, with data from more than 20,000 Swedish consumers patronizing approximately one hundred Swedish companies.…”
Section: Perceived Market Performancementioning
confidence: 99%
“…Furthermore, in a longitudinal study spanning two years, Koys (2001) found that job satisfaction contributed directly to profits for a restaurant chain. Similarly, Keiningham et al (2006) found that employee satisfaction has a positive effect on store profitability for grocery superstores. Clearly a direct relationship also exists between employee job satisfaction and organizational profits, and thus, a parallel proposition to P10b is indicated as well.…”
Section: Effect Of Job Satisfaction On Organizational Outcomesmentioning
confidence: 93%
“…Studies concerning the relationship between the chain elements are recurrent in international journals and specialized magazines publications like Keiningham et al (2006), Gelade and Young (2005), Yingzi (2005), Kassinis and Soteriou (2003). The present study differs from those, both on the studied sector and the aim.…”
Section: Introductionmentioning
confidence: 72%
“…On the other hand, Keiningham et al (2006) explored the relationship between employees´ satisfaction and profitability in studies on a major European supermarket chain and had found results that differ significantly of the exploratory studies lead by Heskett et al (2002), finding no relationship between satisfaction of employees and the profitability of the company.…”
Section: Cluster Analysesmentioning
confidence: 82%